Logic of Law: Criminal Profiling Strategy - Kovalchuk, Olha; Banakh, Serhii (Actual problems of law (Aktual’ni problemi pravoznavstva), 2023)
Criminal profiling is used when making decisions on issues in which the cost of a mistake is a person’s freedom or life, so it is essential to choose a rational approach and maintain objectivity. Applying the scientific method is the first step of a chain of steps that can level up the effects of even the most common subtle forms of bias, conscious or unconscious, that are distorted by context and the psychological state of the decision-maker. Criminal profiling is considered as one of the decision support strategies in criminal justice. Based on a unique set of statistical and dynamic data of a sociological survey of 13,010 convicts who are serving sentences in penitentiary institutions in Ukraine, a cluster model was built to determine significant indicators of criminal recidivism. The conducted empirical analysis gives reasons to conclude that the number of previous convictions, the age at the time of the first conviction, conditional convictions, and early releases causes the maximum influence on the probability of criminal recidivism. Criminal profiling does not provide conclusive evidence to solve a case or lead to a new line of investigation, but it cannot be denied that criminal profiling is not valuable in some, albeit exceptional, cases. Criminal profiling is effective in cases involving hostage-taking, rapists, arson, sexual murders, serial crimes, and identifying the authors of threatening letters. The built cluster model simplifies the understanding of criminal behavior and the relationship between the details of the profile of the criminal and provides support for decision-making in criminal justice, for example, when detecting fraudulent actions, predicting the possibility of recidivism, reducing bias when making pre-trial or trial decisions. However, much more research is needed before criminal profiling becomes widely accepted as a reliable forensic tool. One of the following stages of the research is possible like the classification of convicts according to their probable tendency to recidivism based on the analysis of their statistical and dynamic characteristics.